Результаты исследования черепицы из Херсонеса методом характеристического рентгеновского излучения - Магда, А.В.; Дикий, Н.П.; Медведева, Е.П.; Шляхов, Н.А. (My University, 1994)
Magda A. V., Dikiy N. P., Medvedeva E. P., Shlyakhov N. A. The Research of Roofing Tiles from Chersonessus by Method of Particle Induced X-Ray Emission (PIXE) The building ceramic’s complex was researched by the method of particle induced X-ray emission (PIXE). The object of researches establishment fore the possibility of the roof tile Lo the local industry or to import from other regions. Received results are treated by correlate analyze. The researches have established that 90 per cent of all material were made in Chersonesus and only 10 per cent were imported from other regions.